Challenging Domesticity: Disruptive Representations of Domesticity in Women’s Art, Literature and the Architecture during the 20th and 21st Century - Martin Castillejos, Ana M.; Melero Tur, Sofia; Morales Jareño, Isabel (International Journal of English Studies, 2024)
This article aims to reflect on how the current changes in the context of domesticity are the result of multiple contributions from women working in different fields. It is a collective effort that began to bear fruit in the second half of the 20th century, when an open war against former traditional standards already existed. In that respect, there is a reference to female artists, writers and architects from the last two centuries which calls that notion into question: from artists present at the Women House exhibition celebrated in 2018 at the National Museum of Women in the Arts (Washington D.C., USA), where many described the domestic realm as a trap to female writers and architects who equally defy and revise previous conceptions of domesticity. All in all, it seems clear that the theoretical approach that supports the need to reshape old domesticity standards works in conjunction with many hands-on efforts, some of which will be shown below.